Preparation of Porous γ-Fe2O3@mWO3 Multifunctional Nanoparticles for Drug Loading and Controlled Release - Peng, Hongxia; Huang, Qin; Wu, Tengyan; Wen, Jin; He, Hengping (Current Drug Delivery, 2018)
Background: The use of chemotherapy drug is hindered by relatively low selectivity toward cancer cells and severe side effects from uptake by noncancerous cells and tissue. Thus, targeted drug delivery systems are preferred to increase the efficiency of drug delivery to specific tissues as well as to decrease its side effects. The aims of this paper are develop microwave-triggered controlled-release drug delivery systems using porous γ-Fe2O3@mWO3 multifunctional core-shell nanoparticles. We also studied its magnetic- microwave to heat responsive properties and large specific surface area. We chose ibuprofen (IBU) as a model drug to evaluate the loading and release function of the γ- Fe2O3@mWO3 nanoparticles. Methods: We used a direct precipitation method and thermal decomposition of CTAB template method to synthesize core-shell structured γ-Fe2O3@mWO3 nanoparticles. The specific surface areas were calculated by the Brunauer-Emmett-Teller (BET) method. The load drug and controlled release of the γ-Fe2O3@mWO3 triggered by microwave was determined with ultraviolet-visible spectroscopic analysis. Results: The γ-Fe2O3@mWO3 nanoparticles possesses high surface area of 100.09 m2/g, provides large accessible pore diameter of 6.0 nm for adsorption of drug molecules, high magnetization saturation value of 43.6 emu/g for drug targeting under foreign magnetic fields, quickly convert electromagnetic energy into thermal energy for controlled release by microwave-triggered which was caused by mWO3 shell. The IBU release of over 78% under microwave discontinuous irradiation out classes the 0.15% within 20s only stirring release. This multifunctional material shows good performance for targeting delivery and mWO3 microwave controlled release of anticancer drugs based on all the properties they possess. Conclusion: The porous shell and the introduction of absorbing material not only increased the drug loading efficiency of the nanoparticles but also realized the microwave-stimulated anticancer drug controlled release. The nanoparticles would be very promising for microwave-induced controlled drug release, targeted drug delivery and hyperthermia therapy using microwave.
Keywords: γ-Fe2O3@mWO3